Pengaruh Struktur Kepemilikan, Ukuran Perusahaan dan Kebijakan Dividen pada Manajemen Laba Riil - Budi, I Wayan; Dwija Putri, I G. A. M Asri (E-Jurnal Akuntansi; Vol 25 No 1 (2018)DO - 10.24843/EJA.2018.v25.i01.p05, 2018)
Real earnings management practices can show a good performance in the short term, but in the long term can reduce the value of the company. Three proxy real earnings management is sales manipulation, overproduction and reductions of discretionary expenditures. This study was conducted to obtain empirical evidence about the influence of the ownership structure, company size and dividend policy on real earnings management. This research was conducted in the company listed on the Indonesia Stock Exchange (BEI) in the period 2013-2016. The sampling method used was purposive sampling. Data analysis used is multiple linear regression. Based on the analysis found that institutional ownership has no significant effect on the real earnings management. Managerial ownership has no significant effect on the real earnings management. The size of the company a significant effect on the real earnings management and dividend policy have a significant effect on the real earnings management. Keywords: real earnings management, ownership structure, company size and dividend policy